Non contact Hamstring injuries in sports - Malliaropoulos, Nikolaos G. (CIC Edizioni Internazionali, 2013)
Hamstring muscle injuries are frequent in different sports and are a clinical challenge for Sports Medicine Teams. Injury Mechanics are import to know while assessing the injured athlete. There are at least two distinctly different types of acute hamstring injuries, which are best distinguished by the different injury situations. Classifying the severity of the injury is equally important. Active Range of motion measurements, proper imaging selection and the anatomical location of the injury must be considered. Once the diagnosis is established rehabilitation issues must be considered. Recurrence rate of the injury and prevention are issues that must always be included in our Hamstring Injuries approach as Clinicians.